The Relationship between Self-Efficacy and Subjective Well Being among Tobacco Farmers - Emi Wuri Wuryaningsih; Fitrio Deviantony; Nugroho Dwi Susilowati (Jurnal Keperawatan Padjadjaran, 2020)
Tobacco is the main raw material for cigarette production, so it is a dilemma for farmers when choosing to plant it. Uncertain weather in Indonesia has an impact on the success of tobacco cultivation. This study aimed to analyze the relationship between self-efficacy and subjective well being in tobacco farmers in Jember Regency. This study used a cross sectional design with a proportional random sampling technique with a sample size of 422 tobacco farmers. The research instrument used the General Scale Efficacy questionnaire (α-Cronbach 0.76-0.9), Scale with Life Satisfaction (α-Cronbach 0.87), and Scale of Positive and Negative Experience (α-Cronbach 0.80-0, 84). This study uses Chi Square (CI = 95%). The results showed there was a relationship between self-efficacy and subjective well being in tobacco farmers (p = 0.000; OR = 4.856). The results of this study are tobacco farmers who have self-efficacy can face crop failure, and this is because of the experience of working as a tobacco farmer, which shows that tobacco farmers worked on average for 23 years with experience of crop failure as much as three times. If farmers have more experience, they can know the weaknesses and strengths of tobacco farming to overcome the problems in the scope of tobacco cultivation. Increased work experience, the farmer is getting bolder in making decisions and dare to bear the risk. This study are expected to help the public health office at the Primary Health Care Service to improve psychosocial health promotion efforts through a joint farmer group.